THE EFFECT OF BLOCK GAMES GROUP ON THE DEVELOPMENT OF SOCIAL INTERACTION CHILDREN AGED 5 YEARS OLD IN HELLO KIDS TK KEC. PANCUR BATU THE YEAR 2022 - Elsa dela vista; Juliana Munthe; Tetti Seriati Situmorang; Edy marjuang purba; Cindy Cloudia (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Social interaction needs to be developed from an early age because it affects the next child’s life. One of the efforts so that children can learn to interact socially is at school, teachers must realize how important social interaction is for children, through education children will be easier to reach with the surrounding environment. The lack of social development of children can cause children not to have readiness in socializing with their peers caused by shyness in speaking so that the child prefers to be alone or prefers to go with his parents wherever they go rather than having to join in playing with his friends. To overcome this problem, the researcher implemented a game idea called the "Block Games Group". This game is one of the author’s ideas which is carried out by forming a mini team (small group) in order to create collaboration between teams that can hone children’s social skills so that tolerance and empathy arise for other people or their playmates in interacting. The method used in this study is a quantitative method, the research design used is a quasi-experimental with "One Groups", so that it can be compared between the conditions before treatment and the conditions after treatment.Variable analysis was carried outby using statistical test Wilcoxon test was carried out to take into account two groups of data that were statistically different. Based on the results of the influence test before Block Games Group was conducted on the development of children’s social interactions, it showed that the percentage of children’s social interaction developmentmost of the respondents who haveDevelopment of Children’s Social InteractionNot suitable (Score=<6)namely as many as 13 respondents (43.3%), and a small proportion of respondents thinkDevelopment of Children’s Social InteractionSappropriate (Score=9-10)namely as many as 6 respondents (20.0%). Whereas the effect after Block Games Group has been carried out on the development of children’s social interactions, shows that the percentage of children’s social interaction developmentmost of the respondents who haveDevelopment of Children’s Social InteractionSappropriate (Score=9-10)namely as many as 17 respondents (56.7%)and a small number of respondents thinkDevelopment of Children’s Social InteractionNot sappropriate (Score=<6)that is as many as 3 people (10.0%).